DNA Fingerprinting Based on Repetitive Sequences of Iranian Indigenous Lactobacilli Species by (GTG)5- REP-PCR - Farzaneh Tafvizi; Maryam Tajabadi Ebrahimi (Fasa University of Medical Sciences, 2012)
Background and Objective: The use of lactobacilli as probiotics requires the application of accurate and reliable methods for the detection and identification of bacteria at the strain level. Repetitive sequence-based polymerase chain reaction (rep-PCR), a DNA fingerprinting technique, has been successfully used as a powerful molecular typing method to determine taxonomic and phylogenetic relationships among bacteria. The aim of this study was to evaluate and detect the genetic diversity of lactobacilli species isolated from different sources in Iran. Material and Methods: Twenty strains were isolated from Iranian traditional yoghurt, cheese, and Tarkhineh. PCR-mediated amplification was carried out by degenerate primers. Sequencing was performed after purification of the PCR product. The rep-PCR fingerprinting by (GTG) 5 oligonucleotide primers was conducted for the discrimination and genotypic grouping of isolates. Results: Isolates were deposited as novel stains of lactobacillus casei, brevis, plantarum, and Entrococcus facium in GenBank. Clustering methods were performed on molecular data by NTSYS software, which was also supported by PCO ordination plot. The rep-PCR profiles showed that the 20 isolates produced different banding patterns. In UPGMA dendrogram, three main clusters were formed. Conclusion: According to our findings, rep-PCR appeared to be a very practical method and highly sensitive in the discrimination of the lactobacillus species. The results of sequencing corresponded to the clustering in dendrogram.